1998
DOI: 10.1007/s004120050343
|View full text |Cite
|
Sign up to set email alerts
|

The cenpB gene is not essential in mice

Abstract: Centromere protein B (CENP-B) is a centromeric DNA-binding protein that binds to alpha-satellite DNA at the 17 bp CENP-B box sequence. The binding of CENP-B, along with other proteins, to alpha-satellite DNA sequences at the centromere, is thought to package the DNA into heterochromatin subjacent to the kinetochore of mitotic chromosomes. To determine the importance of CENP-B to kinetochore assembly and function, we generated a mouse null for the cenpB gene. The deletion removed part of the promoter and the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 23 publications
1
82
0
Order By: Relevance
“…CENP-E, CENP-F, INCENP, survivin, MCAK, ZWINT-1, ZW10, MAD-1, MAD-2, BUB1, BUBR1, and BUB3) associate with the centromere during specific stages of the cell cycle. Constitutive proteins CENP-A, CENP-C, and CENP-H are essential for correct kinetochore assembly and function as evidenced by a lethal phenotype in gene knockout and antibody/RNA inhibition studies in mouse, worm, and chicken DT40 cells (13)(14)(15)(16)(17)(18)(19)(20)(21), whereas CENP-B appears to be functionally redundant for centromere activity (22)(23)(24). Numerous gene knockout and inhibition studies have demonstrated that many of the transient proteins have essential roles in normal mitotic functions, such as INCENP, survivin, CENP-E, BUB3, and MAD2 (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…CENP-E, CENP-F, INCENP, survivin, MCAK, ZWINT-1, ZW10, MAD-1, MAD-2, BUB1, BUBR1, and BUB3) associate with the centromere during specific stages of the cell cycle. Constitutive proteins CENP-A, CENP-C, and CENP-H are essential for correct kinetochore assembly and function as evidenced by a lethal phenotype in gene knockout and antibody/RNA inhibition studies in mouse, worm, and chicken DT40 cells (13)(14)(15)(16)(17)(18)(19)(20)(21), whereas CENP-B appears to be functionally redundant for centromere activity (22)(23)(24). Numerous gene knockout and inhibition studies have demonstrated that many of the transient proteins have essential roles in normal mitotic functions, such as INCENP, survivin, CENP-E, BUB3, and MAD2 (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Human centromeric DNA contains the 17-bp "CENP-B box," which directly recruits the centromere protein CENP-B (Masumoto et al 1989). CENP-B knockout mice are for the most part phenotypically normal (Hudson et al 1998;Kapoor et al 1998;Perez-Castro et al 1998) and functional neocentromeres lack CENP-B (Saffery et al 2000). Moreover, CENP-B is absent from the human Y chromosome (Earnshaw et al 1987) and no CENP-B functional homologs have been identified in Xenopus, zebrafish, C. elegans, or Drosophila to date.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…In addition to insufficiency, several lines of evidence have demonstrated that centromeric DNA is also not necessary for the maintenance of centromeres. While CENP-B binding sites are critical for de novo formation of centromeres, the CENP-B protein is nonessential in mice, indicating that as long as preassembled centromeres are inherited, CENP-B binding to centromeres is not required (Hudson et al 1998;Kapoor et al 1998;Perez-Castro et al 1998).…”
Section: The Role Of Dna Sequence In Centromere Specificationmentioning
confidence: 99%